Frequency of hearing impairment in children between the age of 2 to 10 years with middle ear infection - Sultan Badar Munir; Imran Saeed; Sikander Ghayas Khan; Syed Shakeel Ur Rehman; Rabia Ghayas; Madiha Sikander; Fazaila Ehsan (Journal of the Pakistan Medical Association, 2021)
This study was conducted to find out frequency of hearing impairment in middle ear infection. The study design was a cross- sectional survey, conducted from August 2018 to January 2019 in the ENT Department of Children's Hospital Lahore. The data was collected through convenience sampling technique among 52 patients of middle ear infection. The measurements for level of hearing impairment were taken. The data was analyzed using statistical package for social sciences, SPSS 20.0 Out of total 52, There were found 15 (28.8%) had once a month ear infection and 37 (71.2%) had off and 35 (67.3%) patients had mild hearing, 13 (25%) had moderate, 2(3.8%) severe and 2 (3.8%) had normal hearing loss. It was concluded that most of the participants having middle ear infections had hearing loss. Keywords: Hearing Impairment, Middle Ear Infection, Continuous...